Bacterial patterns and antibiotic sensitivity among neonatal sepsis patients in Dr. H. Abdul Moeloek Hospital, Lampung - Ervina, Leni; Busman, Hendri; Berawi, Khairunnisa; Irawan, Bambang; Azizah, Nailul; Yolanda, Jennifer Ester (Paediatrica Indonesiana, 2025)
Background Neonatal infections cause more than 550,000 deaths each year worldwide. Sepsis is a serious neonatal infection, defined as a severe form of infection that causes organ dysfunction. The incidence of neonatal sepsis in Dr. H. Abdul Moeloek Hospital, Lampung increased by 25% from 2017 to 2018 and by 30% from 2018 to 2019. Inappropriate use of antibiotics as therapy can lead to bacterial resistance to the medication. Understanding the most common bacterial patterns and using the guidance of antibiotic sensitivity tests can help health workers determine the empirical antibiotics needed to achieve optimal management, especially in neonatal sepsis patients. Objective To identify bacteria and their antibiotic sensitivity patterns in neonatal sepsis patients at Dr. H. Abdul Moeloek Hospital, Lampung between January and June 2024. Method  Descriptive study was conducted using medical record data from neonates suspected of having sepsis in Dr. H. Abdul Moeloek Hospital Lampung between January and June 2024. Blood culture data and antibiotic sensitivity testing was obtained from medical records. Results Of 65 blood culture of neonates suspected of having sepsis, 31 results were positive (47.6%). The most common microorganisms found were Klebsiella pneumoniae (23%), Burkholderia cepacia (19%), Acinetobacter baumannii (10%), Pseudomonas aeruginosa (10%), Enterococcus faecium (10%) Staphylococcus aureus (10%), Staphylococcus epidermidis (6%), Enterococcus faecalis (6%), Escherichia coli (3%), and Enterobacter cloacae (3%). Based on the sensitivity data calculated using weighted averages, ciprofloxacin (64.7%) and tigecycline (61.1%) showed highest sensitivity across more than five bacterial species. In contrast, ampicillin/sulbactam (96.0%), gentamicin (94.2%), and ceftriaxone (87.7%) had the highest resistance rates. Conclusion The most common bacteria causing neonatal sepsis were Klebsiella pneumoniae and Burkholderia cepacia. Among more than five bacterial species, the highest overall sensitivity was observed to ciprofloxacin and tigecycline, while the highest resistance rates were observed to ampicillin/sulbactam, gentamicin, and ceftriaxone.